2016
DOI: 10.1111/bph.13461
|View full text |Cite
|
Sign up to set email alerts
|

The brain renin‐angiotensin system plays a crucial role in regulating body weight in diet‐induced obesity in rats

Abstract: BACKGROUND AND PURPOSEReduced weight gain after treatment with AT 1 receptor antagonists may involve a brain-related mechanism. Here, we investigated the role of the brain renin-angiotensin system on weight regulation and food behaviour, with or without additional treatment with telmisartan. METHODSTransgenic rats with a brain-specific deficiency in angiotensinogen (TGR(ASrAOGEN)) and the corresponding wild-type, Sprague Dawley (SD) rats were fed (3 months) with a high-calorie cafeteria diet (CD) or standard c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 75 publications
3
21
2
Order By: Relevance
“…In contrast to the effects observed in our studies, it was demonstrated that peripheral treatment with the AT 1 antagonist telmisartan prevented leptin resistance in rats fed a high-calorie/ cafeteria diet (27). Further, TGR(ASrAOGEN) rats, which exhibit glial-specific knockdown of angiotensinogen expression, are small and resistant to weight gain with high-calorie diets (28). It is unclear how species differences, peripheral actions of telmisartan, and developmental or receptor sensitivity changes in the TGR(ASrAOGEN) rats (29) may complicate the interpretation of these studies in concert with the current study.…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast to the effects observed in our studies, it was demonstrated that peripheral treatment with the AT 1 antagonist telmisartan prevented leptin resistance in rats fed a high-calorie/ cafeteria diet (27). Further, TGR(ASrAOGEN) rats, which exhibit glial-specific knockdown of angiotensinogen expression, are small and resistant to weight gain with high-calorie diets (28). It is unclear how species differences, peripheral actions of telmisartan, and developmental or receptor sensitivity changes in the TGR(ASrAOGEN) rats (29) may complicate the interpretation of these studies in concert with the current study.…”
Section: Discussioncontrasting
confidence: 99%
“…Repeated RS was applied over 5 days (d) in accordance with the protocol of Dallman's group . In contrast to that study using lard and sucrose ), we used sweet-tasting chocolate and cookie bars here, which is more in line with our previous work concerning induced obesity, while controls only received chow diet (Miesel et al 2010, Schuchard et al 2015, Winkler et al 2016. As our previous findings showed that ARB treatment reduced both the intake of palatable food and HPA axis activity (Raasch et al 2006, Miesel et al 2012, we supposed that the HPA-RAS crosstalk functionally affects weight control.…”
Section: Introductionsupporting
confidence: 54%
“…One chow-and one CD-fed group of rats was treated with TEL (8 mg/kg bw , once per day by gavage, beginning at d8 until the end of the study). In our previous studies, 8 mg/kg TEL has been repeatedly shown to induce anti-obese efficacy in rats and mice (Muller-Fielitz et al 2011, Miesel et al 2012, Schuchard et al 2015, Winkler et al 2016. For drug administration, TEL was suspended in distilled water by using gum arabic (10% w/v) to achieve final concentrations.…”
Section: Protocolmentioning
confidence: 99%
“…DIO has been associated with an overexpression of angiotensin II, which regulates fluid balance and plays a role in regulating body weight. It has been hypothesized that CAP leads to weight loss by reducing angiotensin II levels . We observed the effectiveness of CAP in the initial weight analyses (Figure A).…”
Section: Discussionmentioning
confidence: 59%